Implementation of foetal e–health monitoring system through biotelemetry. (27th August 2012) - Chourasia, Vijay S.; Tiwari, Anil Kumar
Continuous foetal monitoring of physiological signals is of particular importance for early detection of complexities related to the foetus or the mother's health. The available conventional methods of monitoring mostly perform off–line analysis and restrict the mobility of subjects within a hospital or a room. Hence, the aim of this paper is to develop a foetal e–health monitoring system using mobile phones and wireless sensors for providing advanced healthcare services in the home environment. The system is tested by recording the real–time Foetal Phonocardiography (fPCG) signals from 15 subjects with different gestational periods. The performance of the developed system is compared with the existing ultrasound based Doppler shift technique, ensuring an overall accuracy of 98% of the developed system. The developed framework is non–invasive, cost–effective and simple enough to be used in home care application. It offers advanced healthcare facilities even to the pregnant women living in rural areas and avoids their unnecessary visits at the healthcare centres.